Paroxysmal nocturnal hemoglobinuria in pregnancy: report of a case and literature review - Sepúlveda-Rivera, Cintia María (2019)
Objectives: To describe the perinatal results in a patient with paroxysmal nocturnal hemoglobinuria. Methods: We present the case of a patient diagnosed with paroxysmal nocturnal hemoglobinuria at the Instituto Nacional de Perinatología, Mexico. Case report: The 19-year-old patient presented a 26-week pregnancy and pancytopenia. Infectious, pharmacological and autoimmune etiologies were discarded. Flow cytometry identified paroxysmal nocturnal hemoglobinuria clone type II/III in over 50% of granulocytes and monocytes. During pregnancy, the management consisted in transfusion support and anticoagulation with acenocoumarin. Delivery occurred at 38.5 weeks of gestation. The patient was then referred to a bone marrow transplant unit.